Lerep Tourism Village in Central Java: Its Basic Tourism Development - Djumiarti, Titik; Purnaweni, Hartuti; Amalia, Sefi; Wulandari, Diah (Iapa Proceedings Conference, 2023)
Tourism is one of the highest factors to encourage economic growth. Tourism development in Indonesia is mostly carried out through the development of tourist villages. Tourism must be designed in order to create a positive impact on society, especially related to economic improvement. One of the Tourism Villages in Central Java is Lerep Village located in West Ungaran district, Semarang Regency which has various agrotourism potentials. This study aims to analyze: "How is the tourism development of Lerep Tourism Village?". This study used a qualitative approach with data collection methods through literature, participatory observation and interviews. In this study review based on 3P+4A, i.e. Price, Place, Promotion and Attraction, Access, Amenity, and Ancillary. Reviewed from 3P+4A, the tourism development of Lerep Village has been very good with regarding to environmental conditions and local wisdom as a superior base for its Tourism package. In terms of the price of the tour package, it is quite affordable and in accordance with the facilities provided. The promotion aspect is an aspect that is still not optimal, thus, it is necessary to optimize tourism promotion through social media. The tourist attractions provided are abundantly varied, but to maintain the sustainability of tourism and so that tourism is not monotonous Access to the Lerep Tourism Village is an aspect that needs special attention for policy makers considering that access to the Lerep Tourism Village, such as roads and the availability of public transportation, is very limited.tourism